COVID-19: A Matter of Planetary, not Only National Health - Jowell, Ashley (Am J Trop Med Hyg, 2020)
The COVID-19 pandemic highlights the multidimensional and inseparable connection between human health and environmental systems. COVID-19, similar to other emerging zoonotic diseases, has had a devastating impact on our planet. In this perspective, we argue that as humans continue to globalize and encroach on our surrounding natural systems, societies must adopt a “planetary health lens” to prepare and adapt to these emerging infectious diseases. This piece further explores other critical components of a planetary health approach to societal response, such as the seasonality of disease patterns, the impact of climate change on infectious disease, and the built environment, which can increase population vulnerabilities to pandemics. To address planetary health threats that cross international borders, such as COVID-19, societies must practice interdependence sovereignty and direct resources to organizations that facilitate shared global governance, and thus can enable us to adapt and ultimately build a more resilient world.